The Unquiet Spirit: A Feminist Critique of Conformity and Rebellion in Sudha Murty’s Mahashweta - Menon, Prashasti; Thakur, Vibha Singh (Revista Review Index Journal of Multidisciplinary, 2025)
Sudha Murty’s 2005 Kannada novel Mahashweta, translated into English by the author herself, presents a deceptively simple narrative that belies a profound exploration of the patriarchal structures governing Indian society. On the surface, it is the story of a brilliant young woman, Anupama, whose aspirations are systematically crushed by the traditional expectations of her marital home and her medical condition. However, a deeper reading, particularly through the lens of Indian feminist theory, reveals the novel to be a sharp critique of the systemic oppression of women, the commodification of the female body and intellect and the subtle yet potent forms of resistance available to them. By analyzing the characters of Anupama, her husband Anand, the frameworks established by Indian feminist thinkers like Susie Tharu, Tejaswini Niranjana and the concept of streedharma, this paper argues that Sudha Murty’s novel is not merely a tragic tale but a powerful allegory for the silent rebellion of women constrained by patriarchal norms and the ultimate, haunting failure of those norms to contain the female spirit.